Growth and plant mass of radish fertirrigated with different doses nitrogen - Silva, Patrícia Ferreira da; de Matos, Rigoberto Moreira; BORGES, VITORIA EDICLECIA; DE ALENCAR, ARYADNE ELLEN VILAR; Neto, José Dantas (Revista Ceres, 2016)
The objective of the present study was to evaluate the effect of nitrogen doses applied via fertigation and associated with different types of crop establishment fertilization on growth and biomass of radish. The experiment was conducted in a greenhouse of the Academic Unit of Agricultural Engineering, Federal University of Campina Grande, from April to May 2014. Treatments consisted of five doses of nitrogen fertilizer applied by fertigation (0, 0.7, 1.4, 2.1 and 2.8g per pot) and three types of crop establishment fertilization (humus 2:2; NPK and control), arranged in a 5 x 3 factor design with four repetitions. The 15 treatments were arranged in 60 plots. The nitrogen source used in the study was urea, divided in three applications: the first application was carried out eight days after transplanting, the second, on day 15, and the third, on day 22. The crop establishment fertilization significantly influenced the growth variables and plant mass of the radish on day 35 after transplanting. The highest values of the variables (number of leaves, plant height, bulb diameter, leaf area, fresh mass of the aerial part, dry mass of the aerial part and root/aerial part were observed in the treatment with humus on day 35 after transplanting. The dose of 2.8g nitrogen per pot corresponding to 6.22g of urea per plant provided the highest yield for the variable number of leafs, leaf area and root length on day 35 after transplanting.